PELATIHAN CARA MENGGUNAKAN ALAT TRANSKRIPSI ELAN - Suntoko; M. Januar Ibnu Adham; Novian Ekawaty (Bajang Institute, 2022)
Human voice can be preserved and analysed through realised sound waves with the help of ELAN software. This ELAN software supports language or language analysis segment sound into tangibles and saves them in a file in the ELAN feature itself. The method used in this training is triangulation, with the umbrella being descriptive qualitative. Observation technique to find out what the participants’ desire. The interview technique used by the servant to determine the representation of the respondent's mind after attending this training. Finally, the documentation used to document the movement that has been carried out is by taking photos along with the activity. The results and discussion obtained from the observation are that respondents, especially students and language activists, are enthusiastic about learning more deeply about the operation of this ELAN device. Meanwhile, based on the results of interviews, it is known that the ELAN software is a new thing and can be integrated into matters relating to language documentation in the Balongsari area itself. Documentation of this training is photos during the training event. After this training, the devotee observed that the respondents were interested in learning language transcription technologies such as ELAN.